Being extraordinary: How CEOS' uncommon names explain strategic distinctiveness - Kang, Yungu; Zhu, David H.; Zhang, Yan Anthea (Strategic Management Journal, 2021)
Research summary We build upon recent theories and studies about relational self to explain how a CEO's uncommon name may be related to a firm's strategic distinctiveness. Our theory explains why CEOs with uncommon names tend to develop a conception of being different from peers and accordingly pursue strategies that deviate from industry norms. We further suggest that the positive relationship between CEO name uncommonness and strategic distinctiveness is strengthened by the CEO's confidence, power, and environmental munificence. Using name commonness data from the U.S. Social Security Administration and financial data of 1,172 public firms over a 19‐year period, we find support for our theoretical predictions. Managerial summary Using 19 years of data on 1,172 public firms, we show that firms' distinctive strategies are systematically linked to their CEOs' uncommon names. Psychological studies suggest that individuals with uncommon names tend to have a self‐conception of being different from their peers. Although many people may not have the confidence to exhibit how unique they believe themselves to be, CEOs do—they are generally confident individuals. It is thus predicted that CEOs with more uncommon names tend to pursue strategies that deviate more from their peer firms'. This pattern is even clearer when CEOs have a higher level of confidence, possess greater power, and operate businesses in an environment with more growth opportunities. Looking for unconventional leaders? You can often tell by their names.